2023
DOI: 10.1088/1361-6528/acbeb3
|View full text |Cite
|
Sign up to set email alerts
|

Skyrmion based majority logic gate by voltage controlled magnetic anisotropy in a nanomagnetic device

Abstract: Magnetic skyrmions are topologically protected spin textures and they are suitable for future logic-in-memory applications for energy-efficient, high-speed information processing and computing technologies. In this work, we have demonstrated skyrmion-based 3-bit majority logic gate using micromagnetic simulations. The skyrmion motion is controlled by introducing a gate that works on voltage controlled magnetic anisotropy. Here, the inhomogeneous magnetic anisotropy behaves as a tunable potential barrier/well t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…demonstrated that VCMA can efficiently control the Néel vector in antiferromagnets with perpendicular anisotropy, enabling coherent excitation and manipulation of AFM order. The first-principles calculations further support these findings, with identified VCMA behavior in ultrathin FeRh/MgO bilayers and in materials like L1 0 -MnPd and MgO-capped MnPt AFM films. Therefore, the precise manipulation of the electric field emerges as a promising avenue for realizing a reconfigurable logic gate within AFM materials, offering flexibility in performing different logic functions. , Additionally, an essential aspect of skyrmion-based logic gates lies in the interaction between skyrmions themselves in AFM thin films, particularly the sky–sky topological repulsion, highlighting their tunability and potential for logic operations. Moreover, thoughtful geometric designs are one of the key mechanisms in reconfigurable skyrmion logic gates (RSL) as they grant the ability to exert control over the motion, interaction, and stability of skyrmions, all of which are critical elements for achieving the desired logic operations. , …”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…demonstrated that VCMA can efficiently control the Néel vector in antiferromagnets with perpendicular anisotropy, enabling coherent excitation and manipulation of AFM order. The first-principles calculations further support these findings, with identified VCMA behavior in ultrathin FeRh/MgO bilayers and in materials like L1 0 -MnPd and MgO-capped MnPt AFM films. Therefore, the precise manipulation of the electric field emerges as a promising avenue for realizing a reconfigurable logic gate within AFM materials, offering flexibility in performing different logic functions. , Additionally, an essential aspect of skyrmion-based logic gates lies in the interaction between skyrmions themselves in AFM thin films, particularly the sky–sky topological repulsion, highlighting their tunability and potential for logic operations. Moreover, thoughtful geometric designs are one of the key mechanisms in reconfigurable skyrmion logic gates (RSL) as they grant the ability to exert control over the motion, interaction, and stability of skyrmions, all of which are critical elements for achieving the desired logic operations. , …”
Section: Introductionmentioning
confidence: 73%
“…48−52 Moreover, thoughtful geometric designs are one of the key mechanisms in reconfigurable skyrmion logic gates (RSL) as they grant the ability to exert control over the motion, interaction, and stability of skyrmions, all of which are critical elements for achieving the desired logic operations. 27,50 However, despite all of these advancements, there are persistent challenges related to reconfigurability and the implementation of logic gates, which ultimately impede the practicality of previous approaches. A notable challenge arises in skyrmion-based logic gates, which is the fabrication process of complex designs, particularly for NAND, XNOR, and NOR logic gates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…gates [15][16][17] and racetrack memories [18][19][20]. Some experiments have confirmed that skyrmions can be produced and driven by spin polarized currents at room temperature [21,22], indicating the enormous potential of using skyrmions in the next generation of spin electronic devices.…”
Section: Introductionmentioning
confidence: 98%
“…The non-trivial topology of the skyrmion offers several advantages, such as low driving current density (∼10 6 A m −2 ), high stability and less interaction between neighboring skyrmions even if placed in close proximity, which allows them to stand out from other magnetic configurations such as domain walls. Therefore, magnetic skyrmions are promising for nextgeneration racetrack memories [8,9], logic devices [10][11][12][13], transistors [14] and nano-oscillators [15]. In addition, skyrmions are proposed to have potential in neuromorphic computing [16,17].…”
Section: Introductionmentioning
confidence: 99%